Adaptasi Tanaman Pangan Lokal Terhadap Genangan Banjir - Mudzakkar, Kahar; Najwa, Syafiratun; Sari, Sunita; M, Mustapsyirah; Aulia, Mirza; Farah, Siti; Yunanda, Novia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Global climate change has increased the frequency and intensity of flooding, directly affecting crop production systems, particularly in tropical regions such as Indonesia. Flooding causes hypoxic to anoxic stress in the root zone, thereby inhibiting root respiration, nutrient uptake, and overall plant growth. Local food crops that have been traditionally cultivated over generations generally exhibit better adaptive capacity than introduced varieties. This study aims to examine the adaptive mechanisms of local food crops to flood inundation and their implications for supporting food security. The findings indicate that the adaptation of local food crops includes the formation of aerenchyma tissues, stem elongation and the development of adventitious roots, shifts in respiratory metabolism from aerobic to anaerobic pathways, as well as the involvement of hormones and flood-tolerance genes, such as those found in rice. These adaptive traits highlight the potential of local food crops as important genetic resources for the development of flood-tolerant crop varieties in the future.